2022
DOI: 10.1136/bmjopen-2021-060655
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and renal efficacy and safety of sodium-glucose cotransporter-2 inhibitors in patients without diabetes: a systematic review and meta-analysis of randomised placebo-controlled trials

Abstract: ObjectivesTo assess the cardiovascular and renal efficacy and safety of sodium-glucose cotransporter-2 (SGLT2) inhibitors in patients without diabetes.MethodsWe searched PubMed, MEDLINE, Embase and Cochrane Library for publications up to 17 August 2022. Certainty of evidence was assessed using the Grading of Recommendations, Assessment, Development and Evaluation approach. Random-effects meta-analyses were performed to pool effect measures across studies. Risk ratios (RRs) with 95% CIs are expressed for compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
4
20
0
Order By: Relevance
“…These drugs tend to be well tolerated aside from a moderate increase in risk of bladder and genital infections reflecting the increased glucose content of urine. 133 As noted, promotion of autophagy and of mitophagy/ MB is a key mechanism whereby effective Sirt1 activity can maintain or restore health. It is therefore appropriate to comment on ancillary nutraceuticals which may complement Sirt1 in aiding these processes.…”
Section: Nutraceuticals Can Activate Sirt1 Allosterically or Via Post...mentioning
confidence: 97%
See 1 more Smart Citation
“…These drugs tend to be well tolerated aside from a moderate increase in risk of bladder and genital infections reflecting the increased glucose content of urine. 133 As noted, promotion of autophagy and of mitophagy/ MB is a key mechanism whereby effective Sirt1 activity can maintain or restore health. It is therefore appropriate to comment on ancillary nutraceuticals which may complement Sirt1 in aiding these processes.…”
Section: Nutraceuticals Can Activate Sirt1 Allosterically or Via Post...mentioning
confidence: 97%
“…Curiously, the SGLT2 inhibitory drugs used to treat diabetes-by diminishing renal retention of glucose and hence moderating glycaemiahave been found to be therapeutically useful in heart and renal failure, even in patients who are normoglycaemic. 133 This effect has been traced to their ability to boost Sirt1 and AMPK activity, thereby promoting autophagy, mitophagy and MB. 20 134-137 While blunting postprandial rises in glucose may boost Sirt1 and AMPK activity via a reduction in oxidisable substrate-rather like caloric restriction does 135 138 -there is evidence that these drugs can exert this effect on cells in vitro, including in heart tissue, which does not express SGLT2.…”
Section: Nutraceuticals Can Activate Sirt1 Allosterically or Via Post...mentioning
confidence: 99%
“…123–127 Several meta-analysis of these trials have been published. 128,129 However, in terms of kidney endpoints the most relevant is probably the most recent one published by the Nuffield Department of Population Health Renal Studies Group and the SGLT2 inhibitor Meta-Analysis Cardio-Renal Trialists’ Consortium. 130 Indeed, authors have centered their meta-analysis on kidney disease progression (defined as a sustained ≥ 50% decrease in eGFR, a sustained low eGFR, ESKD, or death from kidney failure), acute kidney injury, and a composite of cardiovascular death or hospitalization for heart failure.…”
Section: Hypertension Management In Ckdmentioning
confidence: 99%
“… 228 Meta-analysis on all 3 SGLT2 inhibitors revealed no association with a higher fracture incidence in non-T2D and T2D patients. 229 , 230 However, a study with 252 diabetic nephropathy patients (CKD stage 3) reported fractures in 8% of patients in the dapagliflozin group and none in the placebo group during a 104-week follow-up. 231 …”
Section: Unexplored Therapeutic Modulators Of Mineral Handling and Va...mentioning
confidence: 99%
“…228 Meta-analysis on all 3 SGLT2 inhibitors revealed no association with a higher fracture incidence in non-T2D and T2D patients. 229,230 However, a study with 252 diabetic nephropathy patients (CKD stage 3) reported fractures in 8% of patients in the dapagliflozin group and none in the placebo group during a 104-week follow-up. 231 In patients with T2D, the SGLT2 inhibitors tofogliflozin and empagliflozin significantly improved vascular pulse wave velocity, suggesting an effect on arterial stiffness.…”
Section: Compendium On Increased Risk Of Cardiovascular Complications...mentioning
confidence: 99%